Measurement of thermal diffusivity and thermal effusivity of solid and liquid photoacoustic technique - Teh, Ee Phing (2001)
The capability of photoacoustic technique in thermal diffusivity measurement has attracted a lot of interest lately. In the experiment, the open photoacoustic cell (OPC) technique was applied for thermal diffusivity measurement on solid materials such as metal, superconductors and soft ferrites. The photoacoustic signal amplitude was captured as a function of modulated frequency and the characteristic frequency, fc, of each sample is computed. Thermal diffusivity was calculated based on the!c and the sample thickness. The way that thermal diffusivity value behaves towards the change of dopant concentration were then investigated. Generally, the thermal diffusivity value measured were between 0.19 to 0.99 cm²/s. The second part of the work concentrated on liquid materials. By applying the basic theoretical approach and redesigning the OPC sample cell, the thermal effusivity value of liquid samples were able to be determined. The samples chosen were distilled water, engine oil, lubricant, edible oil and creamy consumer products. The measured value was in a good agreement with the reported values previously published. The technique was feasible in obtaining thermal effusivity ranged from 0.042 to 0.l59 Wsl/2/(cm²˚C). Thirdly, for liquid samples with low boiling point such as acetone, methanol and ethanol solvents, the PA technique was used to monitor its evaporation time. The sample of interest was placed in a 13.57 mm³ container heated by a 30 mW He-Ne laser beam. As expected, the evaporation time were found to be inversely proportional to the respective boiling points. The fourth part of the work focused on investigation on the protonation process in polyanilines, a kind of conducting polymer. The photoacoustic spectroscopy was obtained where the optical absorption spectrum was plotted against photon energy. Other then this, the Fourier Transform Infrared (FTIR) spectra, thermal diffusivity and scanning electron microscope (SEM) diagram were also examined. Generally, it was found that the fonnula structures before and after protonation were almost similar except the ptotonated polyaniline exhibited higher thennal diffusivity value. The fmal part of the work was mainly on application of the phase shift approach against chopping frequency of the PA technique. The behavior of phase change with sample thickness was investigated. Later, the carrier transport properties of silicon wafer was measured based on the approach. The parameters examined were the surface recombination velocity and diffusion coefficient.